Pengaruh Citra Merek (Brand Image) Dan Gaya Hidup Terhadap Keputusan Pembelian Smartphone Merek I-phone Dalam Perspektif Islam - Zulaiha; Nurlela; Laili Dimyati; Febriansyah (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This research aims to find out how brand image influences the decision to purchase an I-Phone brand smartphone from an Islamic perspective, a case study of management study program students at ITBis Lembah Dempo. The data analysis used is quantitative analysis, namely data analysis that can be described using numbers. This research focuses on Brand Image (X1), Lifestyle (X2), and Purchase Decisions (Y). Based on simultaneous testing or F test, the Sig value has a significant effect on Purchase Decision (Y) which is 0,000 < 0,05 and the result of F-obtained was 18,19 and F- table was 3,10. It can be concluded that H3 is accepted. It means there is a significant effect between Brand Image (X1), Lifestyle (X2) on the Purchasing Decisions (Y) simultaneously.